Prediction of the net energy value of broiler diets. (6th June 2014) - Carré, B.; Lessire, M.; Juin, H.
<x content-type="archive" xml:space="preserve">Abstract</x> Thirty pelleted diets were given to broiler chickens (eight birds per diet; 21 to 35 days of age) for individual in vivo measurements of dietary net energy (NE) value, using three trials with 10 diets/trial. Amino acid formulation of diets was done on the basis of ratios to CP. NE was measured according to the body analysis method. The basal metabolism component of NE values was calculated on the basis of mean metabolic weight using a coefficient obtained in a previous experiment. Information about apparent metabolisable energy (AME) value of diets, AME corrected to zero nitrogen retention (AMEn) and digestibilities of proteins, lipids, starch and sugars was available from a previous publication. In each trial, mean NE/AME ratios of diets varied by about 6%. From the multiple regressions (n=30) expressing NE and AMEn values as functions of digestible component contents, it was deduced that the NE/AMEn ratios assigned to dietary components were 0.760, 0.862, 0.806, 0.690 and 0.602 for CP, lipids, starch, (sucrose+glucose) and fermentable sugars (α-galacto-oligosaccharides and lactose), respectively. The NE/AME ratio of CP was 0.680. Regression calculations showed that the NE values assigned to individual birds (n=240) could also be predicted with diet AMEn values (NE=0.80 AMEn; R2=0.770) or with an equation combining AMEn value and CP/AMEn ratio (R2=0.773). The latter ratio was found to be the only additional parameter that was significant when added in the NE regression scheme based on AMEn.